2012
DOI: 10.1159/000345291
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerable Atherosclerotic Plaque: From the Basic Research Laboratory to the Clinic

Abstract: Coronary heart disease is the commonest cause of death in Western countries, and atherosclerotic plaques that are prone to rupture have been implicated in the pathogenesis of acute coronary syndromes (ACS). Intensive research has been directed at plaque detection, and various invasive methods have been developed thus far that fulfill this purpose and a lot of them are being applied in the clinical setting. Since invasive methods cannot be used for primary prevention, non-invasive imaging modalities are being s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 95 publications
(47 reference statements)
0
10
0
1
Order By: Relevance
“…Acute coronary syndrome (ACS) is one of the most critical clinical syndromes and rupture of vulnerable plaque in the coronary artery is considered to be responsible for the pathogenesis of acute coronary syndrome [1]. Studies have shown the process of in ammation a ects the stability of the atherosclerotic plaque and may be the initiating link of the early stages of atherosclerosis [2].…”
mentioning
confidence: 99%
“…Acute coronary syndrome (ACS) is one of the most critical clinical syndromes and rupture of vulnerable plaque in the coronary artery is considered to be responsible for the pathogenesis of acute coronary syndrome [1]. Studies have shown the process of in ammation a ects the stability of the atherosclerotic plaque and may be the initiating link of the early stages of atherosclerosis [2].…”
mentioning
confidence: 99%
“…Early identification of such plaques could facilitate timely initiation of adequate primary prevention measures, thus diminishing the incidence of acute coronary events [29]. For this purpose, several imaging methods have been proposed, including IVUS, optical coherence tomography (OCT), magnetic resonance imaging (MRI), or MDCT (Table 1), with variable success [30,31,32]. However, the use of many of these methods is mainly confined to experimental studies and has not yet been validated for everyday clinical practice.…”
Section: Plaque Morphology and Compositionmentioning
confidence: 99%
“…Eq. [1] can be used to calculate the field perturbations generated by the magnetic marker depicted in Figure 1a.…”
Section: Spatial Encoding Fieldsmentioning
confidence: 99%
“…In this equation, Df r; u ð Þ is calculated from Eq. [1] and u refers to angle of the device with respect to its own axis (see Fig. 2) and q r ð Þ is the spin density vector.…”
Section: Spatial Encoding Fieldsmentioning
confidence: 99%
See 1 more Smart Citation